The The Influence of Domestic and Global Factors on Inflation in Indonesia: Augmented Vitaliano Model with ECM Approach - wahyu fitrah; Ida Ayu Putri Suprapti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of domestic and global factors on inflation in Indonesia using the Augmented Vitaliano Model. The variables analyzed include domestic factors represented by the money supply (M2), real Gross Domestic Product (GDP), government spending, and global variables represented by world oil prices, and exchange rates. This study uses a quantitative approach with time series data and the Error Correction Model (ECM) method. The results of the study show that all variables become stationary at the first differentiation and have a long-term equilibrium relationship. The regression results show that world oil prices have a positive and significant effect on inflation, while the money supply, real GDP, government spending, and exchange rates have no significant effect partially. However, simultaneously all variables affect inflation. A negative and significant Error Correction Term (ECT) value indicates the existence of an adjustment mechanism from short-term imbalance to long-term equilibrium, with an adjustment rate of 137.69% per quarter, which means that the adjustment process takes place very quickly, which is less than 1 quarter or in 65 days to return to long-term equilibrium. These findings show that inflation dynamics in Indonesia are influenced by domestic economic conditions as well as fluctuations in global energy prices. Therefore, the formulation of inflation control policies needs to consider global economic developments. Further research is suggested to add other macroeconomic variables as well as use longer data periods. Keywords: inflation, domestic factors, global factors, ECM, Indonesia